Preoperative donor urinary UDP-Glc as an independent risk factor for delayed graft function - Ma, Maolin; Han, Fei; Leng, Qianghua; Chen, Xiaorong; Tang, Zuofu; Zhang, Jinhua; Luo, You; Zhang, Yang; Huang, Zhengyu; Na, Ning (Frontiers in Immunology, 2025)
BackgroundExpanded criteria donors (ECD) have the potential to greatly increase the donor organ pool but pose a higher risk of delayed graft function (DGF) post-transplantation. Uridine diphosphate-glucose (UDP-Glc) plays a significant role in extracellular signaling related to tissue damage and retains stability for detection. Donor urinary UDP-Glc level may be an appropriate and effective biomarker for predicting DGF.MethodsRecipients who underwent successful kidney transplantation, with corresponding collection of donor urine samples, between June 2023 and August 2024 were included. We measured preoperative donor urinary UDP-Glc levels and analyzed their correlation with graft recovery. The study was registered in the Clinical Trial Registry (no. NCT06707272).ResultsPreoperative donor urinary UDP-Glc levels were different between immediated, slowed, and delayed graft function subgroups (7.23 vs. 9.04 vs. 10.13 ug/mL, p < 0.001). Donor urinary UDP-Glc level was an independent risk factor for DGF (odds ratio [OR] = 1.741, 95% confidence interval [CI]: 1.311–2.312, p < 0.001). Furthermore, donor urinary UDP-Glc showed a better predictive value for DGF (AUROC = 0.791, 95% CI: 0.707–0.875, p < 0.001), and combining donor urinary UDP-Glc and donor terminal serum creatinine improved the model predictive value for DGF (AUROC = 0.832, 95% CI: 0.756–0.908, Youden index = 0.56, sensitivity = 0.81, specificity = 0.75, PPV = 0.72, NPV = 0.83, p < 0.001). Additionally, the donor urinary UDP-Glc level was related to the recipient serum creatinine level at 1 month post-transplantation (rs = 0.475, p < 0.001).ConclusionsDonor urinary UDP-Glc level is an independent risk factor for DGF and can provide surgeons with a novel strategy to predict DGF earlier and more accurately without invasive procedures.Clinical trial registrationhttps://clinicaltrials.gov, NCT06707272 identifier.